Balanced Shh signaling is required for proper formation and maintenance of dorsal telencephalic midline structures - Himmelstein, Diana S (BioMed Central, 2010)
BACKGROUND: The rostral telencephalic dorsal midline is an organizing center critical for the formation of the future cortex and hippocampus. While the intersection of WNTs, BMPs, and FGFs establishes boundaries within this critical center, a direct role of Shh signaling in this region remains controversial. In this paper we show that both increased and decreased Shh signaling directly affects boundary formation within the telencephalic dorsal midline. RESULTS: Viral over-expression of Shh in the embryonic telencephalon prevents formation of the cortical hem and choroid plexus, while expanding the roof plate. In a transgenic model where cholesterol-lacking ShhN is expressed from one allele (ShhN/+), genes expressed in all three domains, cortical hem, choroid plexus and roof plate expand. In Gli1/2 -/- mutant brains, where Shh signaling is reduced, the roof plate expands, again at the expense of cortical hem and plexus. Cell autonomous activation of Shh signaling in the dorsal midline through Gdf7-driven activated Smoothened expression results in expansion of the Wnt3a-expressing cortical hem into the plexus domain. In addition, developmental stage determines dorsal midline responsiveness to Shh. CONCLUSIONS: Together, these data demonstrate that balanced Shh signaling is critical for maintaining regional boundaries within the dorsal midline telencephalic organizing center.